Impact of Foot Care Education Program Using WhatsApp Group on Knowledge and Foot Care Practice in Diabetic Patients - Yogi Fitriadi; Hari Kusnanto Josef; Cornelia Wahyu Danawati (Faculty of Medicine, Public Health, and Nursing, 2021)
Background: Diabetic ulcers are still one of the complications of diabetes that cause high costs for treatment and cause disability in diabetic patients due to leg amputation. Diabetic ulcers can be prevented by properly controlling blood sugar levels and foot care practice. Primary care doctors can provide knowledge about foot care practice to the community through Whatsapp Group. Whatsapp Group as one of the social media that is easily accessible via mobile phone can be used to carry out health education to the community continuously.Objectives: Determine the impact of foot care education through Whatsapp Group on knowledge and foot care practice of diabetic patients.Methods: Quasi experimental one group pretest and posttest design was be utilized in this study. Samples were obtained by purposive sampling from diabetic patients who visited and participated in Program Penanggulangan Penyakit Kronis activity in a primary healthcare clinic in Semarang at December 2020 until January 2021. Data were analyzed using the Friedman test and post Hoc Wilcoxon test.Results: Thirty six diabetic patients met the inclusion criteria. The median, minimum, and maximum score of the foot care knowledge before education through Whatsapp Group was 10 (4-13) and the score of foot care practice was 40 (21-56). Immediately after education, the score of knowledge was 12 (9-14) and foot care practice was 49.5 (23-69). One month after education, the knowledge score was 13 (9-14) and the foot care practice score was 50 (26-73). From the Friedman test, it was obtained p value = 0.00 (<0.05) and the Wilcoxon post hoc test p value = 0.00 (<0.05) for the knowledge and foot care practice before and immediately-one month after education. The post hoc Wilcoxon test results p value = 0.24 and p value = 0.79 for the score of knowledge and foot care practice immediately and one month after education.Conclusion: Foot care education through Whatsapp Group has an impact on knowledge and foot care practice for diabetic patients. There is an increase in knowledge and foot care practice after providing education through Whatsapp Group.Keywords: Foot Care Education, Whatsapp Group, Knowledge, Foot Care Practice, Diabetes